WORK FATIGUE OF OPERATING ROOM NURSES AND ITS CORRELATION WITH SLEEP QUALITY - Anjaswarni, Tri -; Nissa, Luthfi Choirun; Sepdianto, Tri Cahyo; Bachtiar, Arief (Jurnal Keperawatan, 2025)
Work fatigue in operating room nurses is a critical issue that affects nurse performance and patient safety. Nurses who are exhausted show symptoms such as reduced activity levels, decreased motivation, sleep disturbances and difficulty concentrating. This condition has an impact on the quality of work of operating room nurses and is dangerous for patients. The purpose of this study to analyze the relationship between work fatigue and sleep quality among operating room nurses. This quantitative study utilized a correlational design, involving 20 respondents selected through a total sampling technique, comprising all operating room nurses at Karsa Husada Hospital Batu. Data analysis was conducted using a Spearman Rank Correlational test. The study found moderate levels of work fatigue and poor sleep quality among the participants. There is a significant relationship between work fatigue and sleep quality, with a p-value of 0.001 and r = 0.682, indicating a strong and positive correlation. This means that increased work fatigue resulting in poor sleep quality. Excessive activity in operating room nurses leads to work fatigue, resulting in poor sleep quality. It is recommended that operating room management adjust shift schedules according to worker capacity and provide adequate rest periods to reduce fatigue and improve sleep quality